Penser le divertissement au XVIIe siècle : Pascal, La Mothe Le Vayer et Saint-Évremond - Joubert, Jean-Marc (Verbum – Analecta Neolatina, 2013)
The theme of "entertainment" is very well-known thanks to Pascal, who gave it a considerable metaphysical and religious dimension. However, in the 17th century, there were other, more appeasing ways to consider it, without these being less profound or important. Two examples of this would be La Mothe Le Vayer, in the footsteps of the "light relief" of Montaigne, and the very fine and elegant Saint-Evremond. Comparing the contrasting approches would be an excellent way for the reader to entertain himself.